THE USE OF ADVERTISING AND SOCIAL MEDIA IN TODAY'S TEENAGE LIFESTYLE - Pratomo, Evan Raditya (VCD: Journal of Visual Communication Design, 2020)
Success in an advertisement or social media is very dependent on an attractive visual appearance and what you want to convey. Social media is a means for consumers to share text, image, audio, and video information with each other and with companies, and vice versa. Social media allows marketers to establish a public voice and online presence. They can effectively strengthen other communication activities. Due to their day-to-day immediacy, they can also encourage companies to stay innovative and relevant. This study used the descriptive qualitative method. Data were collected using the method of observation, literature study, and documentation. The analytical method used is Design Review with stages: Descriptive, Formal Analysis, Interpretation, and Evaluation. The results of this study can be used in advertising appropriately by considering the target audience and product characteristics so that it is useful for students and practitioners to increase knowledge about advertising and social media, know the process of reviewing advertisements, and become a reference in designing communicative, aesthetic, and interesting Keywords: Advertising, Social Media, Social Media Advertising Strategy